10.1016/0967-0653(95)96702-7 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: The global consumption of electronic and electrical products has increased the generation of electronic waste (e-waste), which poses environmental and public health concerns. In Vietnam, informal e-waste processing, characterized by unregulated collection and dismantling, is widespread and exposes workers to hazardous substances. However, data on the health status of e-waste workers remain limited, and exposure to phthalates, which are endocrine-disrupting chemicals widely used in electronics, has not yet been evaluated. OBJECTIVE: This study aims to assess the health status of e-waste workers in Vietnam, measure their phthalate exposure levels, and examine associations with health outcomes. METHODS: We conducted a cross-sectional study of adult e-waste workers in Bui village, Vietnam. Trained staff collected demographic, occupational, respiratory, and dietary habit information using a structured questionnaire in Vietnamese. Medical examinations were performed and body composition measurements, blood samples, and urine samples were obtained. Blood samples were analyzed for hematological parameters and several biochemical markers; urine samples were collected for routine urinalysis parameters and phthalate quantification. RESULTS: Field survey data were collected in March 2025, and 253 e-waste workers were recruited. Preliminary descriptive analysis indicated that most participants were female, had low income, and relied on e-waste processing as their primary income. Personal protective equipment, particularly dust masks and gloves, was commonly used. Laboratory measurements of urinary phthalate metabolites were completed by November 2025. CONCLUSIONS: This protocol provides a framework for evaluating the health status, metabolic indicators, and phthalate exposure among e-waste workers in Vietnam and supports occupational health evaluation. The preliminary findings highlight the feasibility of this study, which supports the evaluation of occupational exposure and health outcomes. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): DERR1-10.2196/96702.